Implementasi Aplikasi Sistem Informasi Kearsipan Dinamis Terintegrasi (Srikandi) untuk Pengelolaan Arsip Dinamis di Kantor Kecamatan Basa Ampek Balai Tapan - Eka, Auvelia Septya; Marlini, Marlini (YASIN, 2025)
The digital transformation of dynamic archive management presents a significant challenge for government institutions, particularly at the sub-district level. However, the implementation of digital systems such as the Integrated Dynamic Archival Information System Application (Srikandi) still exhibits gaps that have yet to be extensively explored empirically. This study aims to describe the implementation of the Srikandi application in managing dynamic archives at the Basa Ampek Balai Tapan Sub-District Office. A descriptive quantitative approach was used, with a sample of seven active staff members selected through purposive sampling. Data were collected through observation, questionnaires, and documentation. The questionnaire consisted of 22 items based on two key indicators from the Technology Acceptance Model (TAM): perceived usefulness and perceived ease of use. Validity was tested using the Pearson Product Moment, and instrument reliability reached a Cronbach’s Alpha score of 0.987. Data analysis included tabulation, percentage calculations, and score categorization. The results show that the implementation of the Srikandi application falls into the “very good” category, with perceived usefulness scoring 81.69% and perceived ease of use at 79.16%. The application has been proven to enhance efficiency, accuracy, and accessibility in managing dynamic archives. The study concludes that the Srikandi application has been successfully implemented at the sub-district level and supports the validity of the TAM model in the context of local government archival management.